2015
DOI: 10.1186/s12955-015-0378-2
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation, reliability and validity of the Spanish version of the Quality of Life in Adult Cancer Survivors (QLACS) questionnaire: application in a sample of short-term survivors

Abstract: BackgroundThe aim of this study was to validate the Quality of Life in Adult Cancer Survivors (QLACS) in short-term Spanish cancer survivor’s patients.MethodsPatients with breast, colorectal or prostate cancer that had finished their initial cancer treatment 3 years before the beginning of this study completed QLACS, WHOQOL, Short Form-36, Hospital Anxiety and Depression Scale, EORTC-QLQ-BR23 and EQ-5D. Cultural adaptation was made based on established guidelines. Reliability was evaluated using internal consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 22 publications
2
17
0
1
Order By: Relevance
“…The European Organization for Research and Treatment of Cancer Quality of Life Core Questionnaire (EORTC QLQ-C30) [ 4 ] and the Functional Assessment of Cancer Therapy-Anemia [ 5 ] have been the most frequently used instruments for assessing the QOL of lymphoma survivors. However, these measures do not detect new symptoms and concerns that may arise after patients complete their cancer treatments [ 6 ]. Some studies have used generic measures, such as the 36-Item Short Form Health Survey [ 7 ] to evaluate the QOL of lymphoma survivors [ 8 ] as well; however, it also has limitations because it does not address specific problems experienced by cancer survivors [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The European Organization for Research and Treatment of Cancer Quality of Life Core Questionnaire (EORTC QLQ-C30) [ 4 ] and the Functional Assessment of Cancer Therapy-Anemia [ 5 ] have been the most frequently used instruments for assessing the QOL of lymphoma survivors. However, these measures do not detect new symptoms and concerns that may arise after patients complete their cancer treatments [ 6 ]. Some studies have used generic measures, such as the 36-Item Short Form Health Survey [ 7 ] to evaluate the QOL of lymphoma survivors [ 8 ] as well; however, it also has limitations because it does not address specific problems experienced by cancer survivors [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quality of life evaluation can help to determine the necessary interventions for improving cancer survivor's quality of life. Among the available tools, we used the QLACS questionnaire because it covered different aspects of life among cancer survivors (3). In this study, after the translation process, we evaluated the face, content and construct validity and reliability of the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Today, the rate of breast cancer mortality has reduced because of advancements in its screening and treatment methods. Thus, the percentage of patients living with this cancer is increasing (3). An American study showed that 89.2% of women with breast cancer were alive after five years of cancer diagnosis (4).…”
Section: Introductionmentioning
confidence: 99%
“…Hasil regresi variabel independen komitmen organisasi (X) terhadap variabel dependen whistleblowing (Y) yang diperoleh dari persamaan pertama, dinyatakan sebagai berikut: Tabel 2 diatas, dijelaskan sebagai berikut : (1) Konstanta sebesar 5.433 artinya sikap whistle-blowing dalam skala interval adalah sebesar 5.433 jika tidak ada komitmen organisasi (X 1 ), persepsi tingkat reliabel lebih dari 0,60 (Escobar et al, 2015 Tabel 3 diatas, dijelaskan sebagai berikut: (1) Pada Model 1 / Tingkat I menyatakan komitmen organisasi berpengaruh positif terhadap sikap whistle-blowing pegawai di Perguruan Tinggi Negeri di Kota Bandung dengan nilai signifikansi 0.000, nilai tersebut lebih kecil dari 0.05. (2) Pada Model 2/ Tingkat I menyatakan bahwa variabel persepsi dukungan organisasi (M) berpengaruh positif terhadap sikap whistle-blowing pegawai di Perguruan Tinggi Negeri di Kota Bandung dengan nilai signifikansi 0.000 lebih kecil dari 0.05.…”
Section: Hasil Dan Pembahasanunclassified